1983
DOI: 10.3758/bf03202894
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and spatial integration for electrocutaneous stimulation

Abstract: Three experiments investigated the properties of temporal and spatial integration for electrocutaneous stimulation at absolute threshold level. The duration of pulses delivered to the skin were varied from .1 to 100 msec, and the spatial distribution of stimulation was varied by controlling separation, width, and length of electrodes. For temporal integration, the threshold currents were fitted by the equation (1-1 0 ) , t n = c, indicating that partial integration took place below the critical duration of 1 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
1

Year Published

1985
1985
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 14 publications
0
8
1
Order By: Relevance
“…The finding that threshold generally decreases with contact area of electrodes does not seem to agree with our previous study (Higashiyama & Tashiro, 1983), which showed that when two electrodes were placed side by side on the ventral side of the forearm, threshold is determined by the lateral separation of electrodes, rather than by the area of the electrodes.…”
Section: Effect Of Electrode Configuration On Thresholdcontrasting
confidence: 71%
“…The finding that threshold generally decreases with contact area of electrodes does not seem to agree with our previous study (Higashiyama & Tashiro, 1983), which showed that when two electrodes were placed side by side on the ventral side of the forearm, threshold is determined by the lateral separation of electrodes, rather than by the area of the electrodes.…”
Section: Effect Of Electrode Configuration On Thresholdcontrasting
confidence: 71%
“…Jones (1956) and Wieland (1960) placed a large anode on the ventral surface of the forearm and a small cathode(s) on its dorsal surface. Anderson and Munson (1951), Higashiyama and Rollman (1991), and Higashiyama and Tashiro (1983) placed two same-sized electrodes side by side on the forearm. In these configurations, the distance between the electrodes usually ranges from 2 to 20 em.…”
mentioning
confidence: 99%
“…A pair of rectangular silver electrodes were constructed to fit into a plastic plate (I cm wide x 2.9 cm long) that was strapped to the underside of the subject's right wrist in the vicinity of the ulnar nerve. The size of each electrode was I x .7 cm; the longer side of an electrode faced that of another electrode, with the inner edges separated laterally by a distance of 1.5 cm (for details of electrodes, see Higashiyama & Tashiro, 1983).…”
Section: Apparatusmentioning
confidence: 99%